The performance and analysis of pre-service teachers’ cognitive demands and content domains in primary mathematics education - Rabaza, M.; Mosimege, M. (South African Journal of Higher Education, 2026)
Teacher educators in universities globally and in South Africa struggle to prepare and challenge primary school preservice teachers with mathematics content that demands them to reason at a higher level of cognition. This article provides an analysis of cognitive demands and content domains of fourth-year preservice teachers at a South African university who are trained to teach mathematics in the intermediate phase. In this mixed-method research study, a total of 30 fourth-year students participated in an online Primary Teacher Education (PrimTed) test. The data from the PrimTed online test were analysed using MS Excel version 2207 software and manually sorted to identify higher-order responses to answer the research question. The findings revealed that the fourth-year students performed high on lower-order concepts and low on higher-order concepts. The findings also reveal that preservice teachers performed low on decimals, measurement, and pattern tasks. The conclusion is that teacher education programmes in similar higher education institutions need to emphasise the analysis and interpretation of higher-order thinking skills for fourth-year student teachers